Atomic spectrometry update – a review of advances in environmental analysis. Issue 1 (7th December 2016) - Butler, Owen T.; Cairns, Warren R. L.; Cook, Jennifer M.; Davidson, Christine M.
Abstract : This review covers advances in the analysis of air, water, plants, soils and geological materials by a range of atomic spectrometric techniques including atomic emission, absorption, fluorescence and mass spectrometry. Abstract : This is the 32 nd annual review of the application of atomic spectrometry to the chemical analysis of environmental samples. This update refers to papers published approximately between August 2015 and June 2016 and continues the series of Atomic Spectrometry Updates (ASUs) in environmental analysis 1 that should be read in conjunction with other related ASUs in the series, namely: clinical and biological materials, foods and beverages; 2 advances in atomic spectrometry and related techniques; 3 elemental speciation; 4 X-ray spectrometry; 5 and metals, chemicals and functional materials. 6 In the field of air analysis, highlights within this review period included the development of a new prototype fluorescence instrument for the ultratrace determination of oxidised mercury species, and coupling of elemental analysers to CRDS alongside the development of FTIR and Raman techniques for the improved characterisation of carbonaceous aerosols. In the arena of water analysis, methods continued to be reported for the speciation of As, Cr and Hg species and, following on from last year, Gd species derived from MRI agents discharged at low level from medical facilities into water courses. Improved methods for the determination of legacy compounds such as organoleads and tins made use of plasma techniques that nowadays are more tolerant of organic solvents. Instrumental developments reported included the use of MC-ICP-MS for isotopic tracer studies and a review of TXRF techniques and associated preconcentration procedures for trace element analysis. In the field of plant and soil analysis, there is a welcome trend in that more workers appear to be optimising their analytical methods (or at least checking their performance, e.g. by analysis of CRMs) even if the main purpose of their study is environmental application rather than fundamental spectroscopy. On-going challenges include: the fact that most speciation methods reported are still too complicated, costly or time consuming, for routine use; the need for more and a wider range of CRMs, especially for speciation analysis and for use with laser-based techniques; and the lack of harmonised analytical methodology, which hinders international environmental regulatory monitoring efforts. In geological applications, a variety of techniques have been employed in the drive towards high resolution multi-elemental imaging of complex solid samples. Recent developments in cell design, aerosol transport and data acquisition for LA-ICP-MS, combined with improvements in ICP mass spectrometer design, provided evidence of its potential for very rapid quantitative 3D imaging. Elemental and isotope imaging by NanoSIMS enabled accurate U–Pb dating of mineral domains too small for reliable measurements by LA-ICP-MS. Although megapixel synchrotron XRFS is still in its infancy, it too should open up new horizons in the study of trace and major element distributions and speciation in geological materials and offer a complementary method to other imaging techniques. The deployment of ICP-MS/MS technology has resulted in successful method development to overcome several intractable isobaric interferences in the analysis of geological materials by single quadrupole ICP-MS with LA and solution sample introduction. Many more environmental applications using this approach are likely to be reported in future ASUs.